Antimicrobial activity of Nigella sativa (black seed) oil against Leptospira species - Radzali, Ahmad Rasul (2015)
The antimicrobial activity of Nigella sativa oil was studied against five serovars of Leptospira interrogans which are L. pomona, L. hardjobovis, L. australis, L. canicola, and L. icterohaemorrhagiae. The minimum inhibitory concentration (MIC) was determined using broth microdilution method by observing complete motility inhibition of the Leptospira through dark-field microscopy at various incubation periods (1 hour, 1 day, 3 days, and 7 days). The N. sativa oil was dissolved in dimethyl sulfoxide (DMSO) prior to further dilution in Ellinghausen, McCullough, Johnson and Harris (EMJH) liquid medium with final concentration ranged from 0.1 to 50mg/ml. All Leptospira serovars were sensitive to N. sativa oil dilution at every incubation period with MIC values varying from 0.52 to 5.21mg/ml. Leptospira pomona was more sensitive to N. sativa oil compared to the other strains, with the lowest MIC value obtained in every incubation period (1 hour = 1.56mg/ml, 1 day = 1.56mg/ml, 3 days = 0.78mg/ml, 7 days = 0.52mg/ml), while L. australis was the least sensitive towards N. sativa oil which was 5.21mg/ml at 7-day incubation period. Penicilin G and DMSO were chosen as positive and negative controls for the experiment respectively. There were significant differences among the Leptospira serovars treated with N. sativa oil on MIC values at 1-hour (p = 0.014), 1-day (p = 0.016), 3-day (p = 0.026) and 7-day (p = 0.010) incubation periods. However, there was no significant difference among different incubation periods on the MIC values of N. sativa oil (p = 0.332).